A pesquisa escolar na biblioteca como instrumento potencializador no processo de ensino-aprendizagem: um olhar para o ensino fundamental I - Pacheco, Maria Neuda de Carvalho Ramos (2020)
This research addressed the need to insert school research as an educational practice,emphasizing the educational role of the school library and its informational potential,with the librarian as the main mediator in the teaching-learning process, working in a participatory and collaborative way with teachers in the development and acquisition of informational skills in students in elementary school I. The problem raised in the research was: how can the library contribute to the inclusion of school research as an educational principle in elementary school I? Based on this questioning, the researchoutlined as its main objective: to insert school research in elementary school I, that is, in the classes of the 1st or 5th year of College Module Aracaju. The specific objectives were to: a) make a diagnosis of the BE of College Module Aracaju in relation to the teaching-learning process, looking for elements that can subsidize the pedagogical practice of elementary I; b) elaborate a school research model that can assist in the teaching-learning process, integrating the librarian's performance with teachers and students; c) to propose a product in the form of a booklet that can bring a significant contribution to the understanding of BE as a space for learning and research within the school. The study was characterized as applied research with a qualitative approach, through a bibliographic research, the bibliographic research sought to contemplate the theme of school research and the professional practice of the librarian in the field of information science study. As this is a professional master's research, it was necessary to carry out an intervention and, based on it, develop a product. The intervention site was the library of College Module Aracaju, the population of this research were the teachers and their coordinators of elementary school I, the data collection, took place with the application of semi-structured interviews. The questions asked in the interviews with teachers and pedagogical coordination were elaborated so that, based on their answers, it was possible to establish parameters that would help in the elaboration and structuring of the proposed booklet, meeting the pedagogical and informational needs of teachers and students of Elementary I. While the librarian and teacher are key players in the teaching-learning process, the work of both must be done together, developing and planning pedagogical activities that can facilitate the teaching-learning process.